Prediksi Financial Distrees BRI Syariah Sebelum Pandemi Covid 19 - Sri Febri Astyo Bakti; yudi siyamto (Nur Science Institute, 2022)
In terms of the ability to generate profits, BRI Syariah experienced a significant decline. If this decline is not immediately resolved, it will be disrupted and the possibility of financial distress in banking can occur. The purpose of the study was to determine the financial distress experienced by BRI Syariah before the pandemic, namely 2016-2019. The research method used in this research is descriptive quantitative approach with calculations using modified Z-Score analysis. The results showed that during the last 4 years before the COVID-19 pandemic, BRI Syariah was categorized as a gray area with a Z Score value of 1.1 < Z